Reprocessing and Reuse of Endoscopic Accessories - Bhatia, Vikram; Bhardwaj, Vaishali; Tevethia, Harsh Vardhan (Journal of Digestive Endoscopy, 2021)
Endoscopic accessories are critical devices that breach sterile body sites. They have unique reprocessing difficulties compared with other medical and surgical devices because of their complex structure, narrow lumens, thermolabile construction materials, and application through a semicritical endoscopic device. In addition, there is the possibility of functional derangement of endoscopic accessories with reprocessing, and most are now marketed as single-use devices. While reprocessing of endoscopes has been the subject of numerous societal guidelines, the issue of reprocessing endoscopic accessories and ancillary detachable devices used with the endoscope is seldom addressed. We summarize the existing data on the cleaning and reprocessing of endoscopic accessories.
Keywords: endoscopic accessories; reprocessing; sterilization; biopsy forceps; papillotomes; snares; baskets